Impact of treatment expertise on the outcome of patients with head and neck cancer treated within 6 randomized trials. Issue 12 (17th November 2018) - Bossi, Paolo; Miceli, Rosalba; Benasso, Marco; Corvò, Renzo; Bacigalupo, Andrea; Sanguineti, Giuseppe; Fallai, Carlo; Merlano, Marlo C.; Infante, Gabriele; Dani, Carla; Di Giannantonio, Valerio; Licitra, Lisa
Abstract: Background: We evaluated the impact of center expertise, in terms of number of patients treated, on the overall survival (OS) and progression‐free survival (PFS) of patients with head and neck squamous cell carcinoma (SCC). Methods: We performed a pooled analysis including data from 6 randomized trials in head and neck SCC conducted in Italy. We evaluated the association between OS or PFS and the number of patients recruited by the center. Results: The outcome of 903 patients who had received radiotherapy (RT) was analyzed (median follow‐up 76 months). The hazard ratio (HR) comparing the third and the first quartiles of the distribution of number of patients per center showed an advantage in PFS (HR 0.59, range 0.53‐0.65, P  < .0001) and in OS (HR 0.70, 0.60‐0.81, P  < .0001) for centers with a higher number of patients recruited. A similar benefit was observed in PFS (HR 0.63, 0.60‐0.66) and OS (HR 0.74, 0.69‐0.79) considering the mean number of patients per year. Conclusions: The PFS and OS were longer for patients treated in high‐case‐volume centers.